Attitude motion compensation for imager on Fengyun-4 geostationary meteorological satellite. (September 2017) - Lyu, Wang; Dai, Shoulun; Dong, Yaohai; Shen, Yili; Song, Xiaozheng; Wang, Tianshu
Abstract: A compensation method is used in Chinese Fengyun-4 satellite to counteracting the line-of-sight influence by attitude motion during imaging. The method is acted on-board by adding the compensation amount to the instrument scanning control circuit. The mathematics simulation and the three-axis air-bearing test results show that the method works effectively. Highlights: An attitude motion compensation method for Chinese Fengyun-4 satellite is proposed. The method can counteract the line-of-sight deviation during attitude motion. The compensation is added to the instrument scanning control circuit and executed. An imaging test with the three-axis air-bearing physical simulator is proposed.